2018
DOI: 10.1097/olq.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Mailed Human Papillomavirus Self-Collection With Papanicolaou Test Referral for Infrequently Screened Women in the United States

Abstract: Background Testing for high-risk human papillomavirus (HPV) infection using mailed, self-collected samples is a promising approach to increase screening in women who do not attend clinic screening at recommended intervals. Methods To assess this intervention among high-risk women in the United States, 429 women without a Papanicolaou (Pap) test in 4 or more years (overdue by US guidelines) were recruited from the general population. Participants aged 30 to 65 years were mailed a kit to self-collect a cervico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
(44 reference statements)
4
34
0
Order By: Relevance
“…Our results are similar to the few recent mail-based HPV self-testing programs in the US, which had self-test return rates of at least 64% and HPV prevalence estimates up to 18%. 17,18 It is worth noting that the return rates in US studies, including our study, are noticeably higher than those from large international mail-based programs (pooled return rate of 24%). 7 A potential reason for this is that the US studies required women to provide consent as part of the study process, and this may have resulted in these studies enrolling women who were highly interested in using an HPV self-test.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Our results are similar to the few recent mail-based HPV self-testing programs in the US, which had self-test return rates of at least 64% and HPV prevalence estimates up to 18%. 17,18 It is worth noting that the return rates in US studies, including our study, are noticeably higher than those from large international mail-based programs (pooled return rate of 24%). 7 A potential reason for this is that the US studies required women to provide consent as part of the study process, and this may have resulted in these studies enrolling women who were highly interested in using an HPV self-test.…”
Section: Discussionmentioning
confidence: 52%
“…These findings add to the growing literature of women reporting extremely positive feedback after using an HPV self-test. 17,26,27 The positive feedback in our study is likely due in part to the HPV self-test device that was used. Prior to our pilot study, we conducted formative research with women from Appalachian Ohio to examine their acceptability of different HPV self-test devices.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The post/mail was the lead preference for receiving and returning HPV self‐test kits, although some women and HCPs expressed reservations about its reliability/efficacy. Internationally, mail‐out self‐test screening studies using different settings and designs have shown a wide range of return rates (8–93%) . Fourth, there was a strong preference for HPV self‐testing to happen at home with no support necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, it has been effective in decreasing rates of cervical cancer (Kowalski & Brown, 1994;SEER, 2011). Despite the reported health benefits, the availability of free or low-cost Pap screening and the overwhelming success of screening initiatives, some women diagnosed with cervical cancer have never had a Pap test or were infrequently screened (Centers for Disease Control and Prevention, 2013;Sabatino et al, 2015;Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 99%